Pragmatic strategies in teaching the Romanian language to international students - Bărbuleț, Gabriel-Dan (Swedish Journal of Romanian Studies, 2024)
The following paper examines effective language-teaching strategies for international students learning Romanian amidst the increasing globalization. Addressing challenges faced by diverse learners, the study employs a methodology encompassing literature review, classroom observations, and interviews with experienced instructors. Emphasizing the importance of pragmatic elements in language instruction, the research explores the integration of technology, cultural immersion, and real-world applications to enhance pragmatic competence. Grounded in sociolinguistic theories, the article underscores the role of pragmatic competence in effective communication. Beyond linguistic structures, language instructors are urged to incorporate nuanced elements reflecting Romanian culture. Pedagogical strategies tailored to international students include task-based activities, role-playing, and language immersion. Assessment involves qualitative analysis of student performance, feedback, and proficiency assessments. The article also delves into the role of technology, discussing the integration of virtual reality, online platforms, and multimedia resources for immersive learning. The study concludes with implications for educators, curriculum developers, and policymakers, advocating for culturally sensitive language curricula. Overall, it contributes to the discourse on language education by emphasizing the interconnectedness of language and culture, promoting pedagogical approaches that foster cross-cultural communication.